Coherent elastic neutrino-nucleus scattering (CEνNS) event rates for Ge, Zn and Si detector materials - Kosmas, T.S.; Kota, V.K.B.; Papoulias, D.K.; Sahu, R. (HNPS Advances in Nuclear Physics, 2022)
Realistic nuclear structure calculations are presented for the event rates due to coherent elastic neutrino-nucleus scattering (CEνNS), assuming neutrinos from pion-decay at-rest, from nuclear reactors and from Earth’s interior. We focus on the currently interesting Germanium isotopes, 70,73,76Ge, which constitute detector materials of the recently planned CEνNS experiments. We study in addition the potential use of 64,70Zn and 28Si isotopes as promising CEνNS detectors. From nuclear physics perspectives, recently, calculations have been carried out within the framework of the deformed shell-model (DSM), based on realistic nuclear forces, and assessed on the reproducibility of spectroscopic nuclear properties. The high confidence level acquired by their agreement with experimental results and by their comparison with other mostly phenomenological calculations encouraged the use of DSM to extract predictions for the CEνNS event rates of the above isotopes. Our detailed estimation of the nuclear physics aspects of the recently observed neutral current coherent neutrino-nucleus scattering may shed light on unravelling the still remaining uncertainties for the CEνNS process within and beyond the Standard Model.